Animal models of antiphospholipid syndrome - Ren, Chunyao; Li, Hongbin; Ren, Tingting (Frontiers in Immunology, 2026)
Antiphospholipid syndrome (APS) is an autoimmune disorder defined by persistent antiphospholipid antibodies (aPL), thrombosis, and/or pathological pregnancy. Its phenotypic spectrum is heterogeneous and its pathogenesis remains incompletely understood. The incidence of APS increases year by year. Due to the constraints on human studies, animal models have become indispensable tools for dissecting the mechanisms of APS. The animal models accelerate the drug discovery and refine the therapeutic strategies in APS. Over the past decades, substantial methodological and translational advances have been achieved in APS animal models. In this review, we systematically summarize the current construction paradigms in thrombotic and obstetric APS animal models and highlight their respective advantages and limitations.